Induced Pluripotent Stem Cells: Generation Strategy and Epigenetic Mystery behind Reprogramming - Pengfei Ji; Sasicha Manupipatpong; Nina Xie; Yujing Li (Stem Cells International)
Possessing the ability of self-renewal with immortalization and potential for differentiation into different cell types, stem cells, particularly embryonic stem cells (ESC), have attracted significant attention since their discovery. As ESC research has played an essential role in developing our understanding of the mechanisms underlying reproduction, development, and cell (de)differentiation, significant efforts have been made in the biomedical study of ESC in recent decades. However, such studies of ESC have been hampered by the ethical issues and technological challenges surrounding them, therefore dramatically inhibiting the potential applications of ESC in basic biomedical studies and clinical medicine. Induced pluripotent stem cells (iPSCs), generated from the reprogrammed somatic cells, share similar characteristics including but not limited to the morphology and growth of ESC, self-renewal, and potential differentiation into various cell types. The discovery of the iPSC, unhindered by the aforementioned limitations of ESC, introduces a viable alternative to ESC. More importantly, the applications of iPSC in the development of disease models such as neurodegenerative disorders greatly enhance our understanding of the pathogenesis of such diseases and also facilitate the development of clinical therapeutic strategies using iPSC generated from patient somatic cells to avoid an immune rejection. In this review, we highlight the advances in iPSCs generation methods as well as the mechanisms behind their reprogramming. We also discuss future perspectives for the development of iPSC generation methods with higher efficiency and safety.